Characterization of CYP2D6 Pharmacogenetic Variation in Sub‐Saharan African Populations. Issue 3 (21st October 2022) - Twesigomwe, David; Drögemöller, Britt I.; Wright, Galen E.B.; Adebamowo, Clement; Agongo, Godfred; Boua, Palwendé R.; Matshaba, Mogomotsi; Paximadis, Maria; Ramsay, Michèle; Simo, Gustave; Simuunza, Martin C.; Tiemessen, Caroline T.; et al.
Abstract : Cytochrome P450 2D6 (CYP2D6) is a key enzyme in drug response owing to its involvement in the metabolism of ~ 25% of clinically prescribed medications. The encoding CYP2D6 gene is highly polymorphic, and many pharmacogenetics studies have been performed worldwide to investigate the distribution of CYP2D6 star alleles (haplotypes); however, African populations have been relatively understudied to date. In this study, the distributions of CYP2D6 star alleles and predicted drug metabolizer phenotypes—derived from activity scores—were examined across multiple sub‐Saharan African populations based on bioinformatics analysis of 961 high‐depth whole genome sequences. This was followed by characterization of novel star alleles and suballeles in a subset of the participants via targeted high‐fidelity Single‐Molecule Real‐Time resequencing (Pacific Biosciences). This study revealed varying frequencies of known CYP2D6 alleles and predicted phenotypes across different African ethnolinguistic groups. Twenty‐seven novel CYP2D6 star alleles were predicted computationally and two of them were further validated. This study highlights the importance of studying variation in key pharmacogenes such as CYP2D6 in the African context to better understand population‐specific allele frequencies. This will aid in the development of better genotyping panels and star allele detection approaches with a view toward supporting effective implementation of precision medicine strategies in Africa and across the African diaspora.